1974
DOI: 10.21273/jashs.99.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Appraisal of the Relationship of Seed Abortion to Chemical Induction of Apple Fruit Abscission Following Bloom1

Abstract: Histochemical examination of apple seeds (cv. Golden Delicious) from persisting and abscising fruit were conducted 2 days after treatment (NAA, 30 ppm; Sevin, 2 lb./100 gal water). Seeds and embryos of NAA-treated potential drop fruit were appreciably smaller than those associated with other treatments. There was no evidence of reduced levels of nucleic acids, proteins, or starch in embryo or endosperm when compared with corresponding tissue from untreated persistent fruit. The extent of starch deposition in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Starch gran ules, identified by PAS staining, could easily be seen in cleared ovules. Their relative abundance indicates advancing maturity( 12) and substantiated other embryo sac data on relative ovule development in the 3 orchards. Our observations agree with those of Bini and Bellini (1) who failed to find evidence of early degeneration of 'Comice' embryo sacs.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Starch gran ules, identified by PAS staining, could easily be seen in cleared ovules. Their relative abundance indicates advancing maturity( 12) and substantiated other embryo sac data on relative ovule development in the 3 orchards. Our observations agree with those of Bini and Bellini (1) who failed to find evidence of early degeneration of 'Comice' embryo sacs.…”
supporting
confidence: 80%
“…Temperature during growth has a pronounced influence on flower and shoot development of several greenhouse rose culti vars (1,4,9,10,11,12,13,14,17). However, the maintenance of recommended growing temp can be costly during the summer months when considerable cooling may be required and during the winter when heating is required.…”
Section: Methodsmentioning
confidence: 99%
“…Flagging consists of leaf rolling, drooping, and curling of the young shoot tips. At 1 to 2 days after NAA treatment, decreased movement of exogenously applied la belled sucrose to the developing fruit has been detected (7,12). Crowe (2) reported that NAAm reduced the levels of auxin-like exudate from sprayed fruits 1 day after treatment.…”
mentioning
confidence: 99%